Landasan Perkembangan Iptek dan Pengembangan Kurikulum PAI pada Mata Pelajaran Al-Qur’an Hadist di Madrasah Tsanawiyah: The Foundation of Science and Technology Development and Curriculum Development of Islamic Education in the Subject of Qur’an and Hadith at Madrasah Tsanawiyah - Ramadhannita, Retno Dwi (Perkumpulan Peneliti dan Pegiat Literasi, 2022)
Curriculum development in the Al-Qur'an Hadith subject plays a crucial role in shaping students' critical and analytical thinking abilities. This study aims to evaluate the impact of the development of Science and Technology (IPTEK) on curriculum development, particularly in the context of learning Al-Qur'an and Hadith at the Madrasah Tsanawiyah (MTs) level. The research employs a qualitative method within a descriptive research framework. The findings indicate that the integration of IPTEK in learning has a positive impact on students. The diversity of learning resources, involving not only books but also technology, makes the learning process more engaging and effective. Teachers have successfully integrated the foundations of science and technology with curriculum development in the Al-Qur'an Hadith subject, as evidenced by student testimonials stating that the use of technology significantly aids the learning process. The implications of this study are for educators and curriculum developers to continue expanding the integration of IPTEK in teaching to enhance the quality of education in Madrasah Tsanawiyah. Keywords: Curriculum Development, Science and Technology, Islamic Religious Education, Al-Qur'an Hadith, Madrasah Tsanawiyah Abstrak: Pengembangan kurikulum pada mata pelajaran Al-Qur’an Hadis memainkan peran penting dalam membentuk kemampuan berpikir kritis dan analitis siswa. Penelitian ini bertujuan untuk mengevaluasi pengaruh perkembangan Ilmu Pengetahuan dan Teknologi (IPTEK) terhadap pengembangan kurikulum, khususnya dalam konteks pembelajaran Al-Qur’an dan Hadis di tingkat Madrasah Tsanawiyah (MTs). Metode penelitian yang digunakan adalah kualitatif dengan kerangka penelitian deskriptif. Hasil penelitian menunjukkan bahwa integrasi IPTEK dalam pembelajaran memiliki dampak positif terhadap siswa. Keanekaragaman sumber belajar, yang melibatkan tidak hanya buku tetapi juga teknologi, membuat proses pembelajaran menjadi lebih menarik dan efektif. Guru telah berhasil menggabungkan dasar-dasar ilmu pengetahuan dan teknologi dengan pengembangan kurikulum pada mata pelajaran Al-Qur’an Hadis, sebagaimana dibuktikan oleh kesaksian siswa yang menyatakan bahwa penggunaan teknologi sangat membantu proses pembelajaran. Implikasi dari penelitian ini adalah bagi para pendidik dan pengembang kurikulum untuk terus memperluas integrasi IPTEK dalam pengajaran, guna meningkatkan kualitas pendidikan di Madrasah Tsanawiyah. Kata Kunci: Pengembangan Kurikulum, Ilmu Pengetahuan dan Teknologi, Pendidikan Agama Islam, Al-Qur’an Hadis, Madrasah Tsanawiyah